(untitled) (Historia, 2021)
This is the first of two articles in which the authors try to establish at least part of the reasons why the Afrikaners, with their strong democratic antecedents of the nineteenth century, became the perpretators of undemocratic practices after 1948. The pioneer circumstances of the nineteenth century and the regard for patriarchs produced the possibility of both a democratic and an authoritarian development. Calvinism as a source of Afrikaner political thought is largely discarded by the authors, but the Enlightenment played a significant role in the nineteenth-century political theory. However, it appears that the patriarchal tradition won from the pioneer situation and the Enlightenment, as the legislatives of the two Boer republics jealously protected their powers and claimed full and unfettered powers inbetween elections.